The New Israel: The evolution of the idea and image among Christian nations. Issue 3 (19th February 2020) - Malach, Assaf
Abstract: This article deals with the use made by Christian people of the image of a chosen people for national and political purposes, while identifying a specific Christian nation or kingdom as the "New Israel." It begins by describing the idea of "New Israel" as a pan‐Christian idea that underwent a fundamental change when its use began with reference to a specific nation. The article continues with a detailed mapping of the phenomenon in Ethiopian Christianity, in the Catholic world in the Middle Ages, in the Russian Orthodox world, and in the Protestant countries in the early days of the modern era. The article describes the broad context of the phenomenon in the framework of ethnocentric imagery in different cultures and the continuation of the research required for its full description. This phenomenon is interesting because it indicates the importance that many people attributed in the premodern period to the formulation of a national narrative and the centrality of religion in formulating a national narrative during this period. It emphasizes the political inspiration that Europe drew from the Bible in the formulation of national narratives, as well as the prominence of the national idea in the Bible itself, which made it an accessible source of inspiration for national ideas of Christian people.